Sleep disordered breathing from preschool to early adult age and its neurocognitive complications: A preliminary report - Astara, Kyriaki; Siachpazidou, Dimitra; Vavougios, George D; Ragias, Dimitrios; Vatzia, Konstantina; Rapti, Georgia; Alexopoulos, Emmanouil; Gourgoulianis, Konstantinos I; Xiromerisiou, Georgia (Sleep Science, 2021)
Objective The onset and development of sleep disordered breathing (SDB) remains unclear in an age - dependent manner. Despite treatment, persistent symptoms such as snoring and excessive daytime sleepiness, as well as cognitive impairment may be present. The aim of the research was to determine the prevalence of residual symptoms of SDB in adolescence and early adulthood, the predisposing factors and its neurocognitive complications.Methods In the present pilot study-cohort, a questionnaire was utilized to 154 people (average age: 17.9 ± 3), who as children (mean age: 5.3 ± 1.4) had AHI ≥2.5 episodes/h. They were divided into two groups based on AHI = 5 episodes/h. Depending on the results, they were invited to undergo a repeated polysomnography (PSG) and complete the Montreal Cognitive Assessment (MoCA) test. Statistical analysis was made with IBM SPSS software.Results Out of the total, 35.7% claimed to still snore. AHI was negatively correlated to the severity of residual symptoms (Mann-Witney U test, p <0.005). According to repeated PSGs, 9/17 met the criteria for OSAS, while high BMI was associated with the severity of new AHI (chi squared test, p<0.005). Additionally, 7/16 scored below the MoCA baseline (<26/30). The characteristics of cognitive declines were mapped, with most prominent having been visuospatial, short - term memory and naming/language deficits.Discussion A significant percentage of children with sleep breathing disorder present with residual symptoms during their transition to early adulthood, as well as undiagnosed neurocognitive complications. Clinicians suspicion for the underlying neurocognitive complications is required, even in young adults, while guidelines on monitoring pediatric OSAS patients after treatment should be addressed.
Keywords: Sleep Apnea Syndromes; Cognitive Dysfunction; Adolescent; C-Reactive Protein